Kegiatan Penyuluhan Fisioterapi Tentang Skoliosis Pada Kelompok Remaja di Posyandu Remaja Bakalankrajan Malang - Faidhul Lathifatun Nur; Rakhmad Rosadi; Indah Ningtiyas Hidayanti (Universitas Maritim AMNI Semarang, 2024)
In this increasingly advanced era marked by increasing technology and demands for understanding science, the younger generation must study hard. At school, teenagers are often not ergonomic in carrying out an activity, one of which is carrying a bag on one side and maintaining the wrong posture for a long time. Wrong postural patterns can cause musculoskeletal problems, one of which is scoliosis. Scoliosis is a spinal deformity characterized by a sideways curved curve with or without spinal rotation. One of the ways to reduce the risk of scoliosis is by providing education. The aim of this counseling is expected to be able to provide education to adolescents in order to reduce the risk of scoliosis in Bakalan Krajan Village, Malang. The method used is to conduct education using leaflet media. The results of this activity were that the participants showed a positive attitude while participating in the community service activities from start to finish. This counseling activity can increase adolescents' knowledge and understanding of scoliosis.